Association of Polymorphisms of Phase I Metabolizing Genes with Sister Chromatid Exchanges in Occupational Workers Exposed to Toluene Used in Paint Thinners. (24th November 2015) - Priya, Kanu; Yadav, Anita; Kumar, Neeraj; Gulati, Sachin; Aggarwal, Neeraj; Gupta, Ranjan
Abstract : This study investigated genetic damage in paint workers mainly exposed to toluene as it is a major solvent used in paint thinners. Sister chromatid exchange (SCE) assay was used as biomarker of genotoxicity. Blood samples were collected from 30 paint workers and 30 control subjects matched with respect to age and other confounding factors except for exposure to toluene. SCE frequency was found to be significantly higher in paint workers (4.81 ± 0 . 92 ) as compared to control individuals (1.73 ± 0 . 54 ) (p < 0.05 ). We also investigated influence of polymorphisms of CYP2E1 and CYP1A1m2 genes on SCE frequency. Our results showed that there was significant increase in frequencies of SCE among the mutant genotypes of CYP2E1 and CYP1A1m2 as compared to wild genotypes. Our study indicated that long term exposure of toluene can increase genotoxic risk in paint workers.